Batman begins, Training Bruce Wayne - Kowitt, Holly (New York : Scholastic, 2005)
Bruce Wayne learns martial arts in a monastery. When he completes his training he is expected to lead a team of ninjas to detroy Gotham city but instead he leaves to become Batman.
"Based on the new movie!"-- on cover.
Keywords: Batman (Fictitious character) -- Juvenile fiction; Good and evil -- Juvenile fiction; Martial arts -- Juvenile fiction; Fear -- Juvenile fiction; Batman (Fictitious character) -- Fiction; Good and evil -- Fiction; Martial arts fiction; Fear -- Fiction